Impact of omission of surgery on survival of older patients with breast cancer. Issue 11 (4th August 2014) - de Glas, N. A.; Jonker, J. M.; Bastiaannet, E.; de Craen, A. J. M.; van de Velde, C. J. H.; Siesling, S.; Liefers, G.‐J.; Portielje, J. E. A.; Hamaker, M. E.
<x xml:space="preserve">Abstract</x> Background Older patients with breast cancer are often not treated in accordance with guidelines. With the emergence of endocrine therapy, omission of surgery can be considered in some patients. The aim of this population‐based study was to investigate time trends in surgical treatment between 1995 and 2011, and to evaluate the effects of omitting surgery on overall and relative survival in older patients with resectable breast cancer. Methods Patients aged 75 years and older with stage I–III breast cancer diagnosed between 1995 and 2011 were selected from the Netherlands Cancer Registry. Time trends of all treatment modalities were evaluated using linear regression models. Changes in overall survival were calculated by Cox regression. Relative survival was calculated using the Ederer II method. Results Overall, 26 292 patients were included. The proportion of patients receiving surgical treatment decreased significantly, from 90·8 per cent in 1995 to 69·9 per cent in 2011 (P < 0·001). Multivariable analysis showed that overall survival did not change over time (hazard ratio 1·00 (95 per cent confidence interval (c.i.) 0·99 to 1·00) per year); nor did relative survival (relative excess risk 1·00 (0·98 to 1·02) per year). Conclusion Omission of surgery has become more common in older patients with breast cancer during the past 15 years in the Netherlands, but this has not altered overall or relative survival.